2021
DOI: 10.3390/catal11020261
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag-TiO2/Sr4Al14O25:Eu2+,Dy3+ Photocatalyst on Phosphor Beads and Its Photoreaction Characteristics

Abstract: Long-lasting Sr4Al14O25:Eu2+,Dy3+ phosphor beads were prepared with inorganic sodium silicate binders and coated to support Ag-doped TiO2 catalyst by the sol–gel coating method. Energy dispersive spectroscopy and X-ray photoelectron spectroscopy confirmed that Ag and TiO2 were loaded on the bead surface. Photocatalytic degradation of toluene volatile organic compound was evaluated under ultraviolet and visible light through 410 nm filters. The photocatalyst/phosphor beads of Ag-TiO2/Sr4Al14O25:Eu2+,Dy3+ decora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…For example, N-doped TiO 2 /WO 3 has excellent catalytic performance under visible light [70]. In addition, some noble metal elements like Ag may also enhance the light absorption of photocatalysts by surface plasmon resonance [72]. The doping of some transition metal and non-metal elements, such as V, Zr, Cr, Mn, N, etc., may introduce vacancies or defects in the catalyst crystals, and these vacancies or defects often perform as highly active reaction sites in reactions [52].…”
Section: Doping Of the Metal-containing Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, N-doped TiO 2 /WO 3 has excellent catalytic performance under visible light [70]. In addition, some noble metal elements like Ag may also enhance the light absorption of photocatalysts by surface plasmon resonance [72]. The doping of some transition metal and non-metal elements, such as V, Zr, Cr, Mn, N, etc., may introduce vacancies or defects in the catalyst crystals, and these vacancies or defects often perform as highly active reaction sites in reactions [52].…”
Section: Doping Of the Metal-containing Photocatalystsmentioning
confidence: 99%
“…As for the problem of the recovery of nanoparticle photocatalysts, Eun S.R. et al [72] developed Ag-TiO 2 /Sr 4 Al 14 O 25 : Eu 2+ , Dy 3+ phosphor beads' nano photocatalysts for the degradation of toluene by UV/Vis via a sol-gel coating method. The photocatalyst had higher catalytic activity due to the doping of Ag element and was conducive to the recycling of nano materials to prevent secondary pollution.…”
Section: Noble Metal and Rare Metal Dopingmentioning
confidence: 99%
“…[ 201 ] It was also claimed that it could be used as a photocatalyst. [ 202 ] Degradation of toxic materials [ 203 ] such as organic dyes [ 204 ] to some harmless form can be achieved using photocatalysis with LLP materials. Carlos et al [ 205 ] found enhancement in photocatalytic activity due to Bi 3+ codoping.…”
Section: Aluminate Phosphors For Applicationsmentioning
confidence: 99%
“…Photocatalytic activity of the prepared SAOs was higher than TiO 2 photocatalyst due to higher photosensitivity and lower band‐gap of the SAOs compared to TiO 2 . Thus, several phosphors have been used as effective photocatalysts for degradation of different types of pollutants (Eun et al, 2021; Li et al, 2012; Ma et al, 2013; Naorem et al, 2020). In fact, the phosphors are known as luminescence‐assisted photocatalysts which use their long afterglow as a light source to carry out the photocatalytic reaction (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%